A new model of socio-economic development of Slovakia - Koloman Ivanička (European Regional Science Association (ERSA), 2012)
Slovakia is on route for searching its development model. It required courage to take bridge programs for invention, innovation and creativity. A new culture is created in relation to the third industrial revolution. It relies on the dispersion potential, universally available energy sources, energy storage using hydrogen, and the new association energy and information technologies. Slovakia has a chance within 20 to 25 years to achieve energy self-sufficiency. A major reconstruction will be difficult to source and change approaches, i.e. knowledge society. The company has to learn the fact that the advent of the era of non-waste is a possible theory living planet Gaia can be translated into reality. The mental system becomes more 'people oriented system - the human-oriented system and earth centered system - the planet Earth concentrated economics'. M. Albert promotes participatory democracy (Parecom) and D. Schweickart economic democracy, in which much or all classes of the population that the operation involved in the economic system. An important role will play an innovative, creative center (Ideopolises). Noteworthy is the connection of classical genius loci of a new morfic resonance. A significant amount of innovation is transforming creative environment. Without its support function starts outflow inventive and creative people from the territory of the region state. After leaving their lack of capital formation, or transfer of capital. Regions of emigration are changing for place of poverty. Creating a successful, sustainable social model is not creative and inventive talents of people difficult and hardly feasible. Stability, and independence self government. State may be endangered. Slovakia is undoubtedly a vital country, able to go forward with a dynamic European nations and states. Located in the heart of Europe and is a natural crossroads and ideas. It has resources, talents, social and technical infrastructure, but must be used properly. Slovakia can create own image, own branding developed countries, to demonstrate its genius loci, its ability to gain cooperation with foreign countries and support from abroad. It has all the prerequisites to handle a challenge of a new model of its innovative development in the spirit of the requirements of the World Summit Rio +20.
Keywords: O10; 330; The direction of the third industrial revolution; people oriented system; earth centered economy; economic democracy; morfic resonance; memory space; genius loci; creative environment; Slovakia potential for invention; innovation and creativity; consciousness and restructuring space